Characterization of overactive bladder in women in a primary care setting - Cheung, Wellman W (Dove Medical Press, 2011)
BACKGROUND: Overactive bladder (OAB) represents a disorder with overall increasing prevalence in the American population. However, gender-specific characteristics of OAB and how it relates to the general practitioner are not well described. We sought to determine the distribution and characteristics of OAB in women in a primary care setting. METHODS: Self-administered questionnaires were distributed to patients visiting a family medicine outpatient center. The modified questionnaire included eight questions on evidence of lower urinary tract symptoms (LUTS, OAB-validated 8-question screener [OAB-V8]), two questions on stress urinary incontinence, and one question on incomplete emptying. The questionnaire included demographic characteristics and relevant medical and surgical history. Body mass index was calculated based on weight and height. Chi-square test and risk ratio analysis were used to analyze the relationship between OAB and other independent variables. RESULTS: Of 1025 questionnaires administered, 386 were completed. Patients ranged from 16 to 97 years, the majority were African American (78.2%), and 49.7% were premenopausal while 50.3% were postmenopausal. OAB was present in 46.4% of premenopausal women and 41.7% of postmenopausal women. OAB was significantly associated with overweight status (body mass index 25.0–29.9, P = 0.042) and obesity (body mass index ≥30, P < 0.001). Overall, obese women were twice as likely to have OAB (relative risk = 1.99, 1.31–3.04) than women with normal weight. OAB was not shown to correlate with race, cigarette use, history of hysterectomy, or parity. CONCLUSION: OAB was evident in 44% of all female patients surveyed, which is much higher than previously reported estimates. In addition, overweight women were more likely to have OAB. Increased awareness of OAB in the primary care setting should be considered for women’s general health.